(untitled) (Conversatoria Linguistica, 2019)
The article presents observations related to communication based on a dialog with a man diagnosed with dementia of the Alzheimer type (6 stage according to the Global Deterioration Scale). The essential aim of the research was to determine the range of possibilities and means of communication available to the patient. Attention was paid to the patient’s interactions, taking into account such aspects as supporting interaction and withdrawal from it. In the article the author presents some strategies of compensation and escapism that the patient used during conversations.